Assessment of immunohematological, hematological and biochemical responses in cultivable fish Cyprinus carpio exposed to an antibiotic sulfamethoxazole (SMX) - Nazish Iftikhar; Imran Hashmi (IWA Publishing, 2021)
Sulfamethoxazole (SMX) is a member of the sulfonamides group of antibiotics which is used extensively in aquaculture throughout the world. In this study, common carp (Cyprinus carpio) was used as the bioindicator to assess the toxicity potential of SMX. Effects were based on chronic toxicity of environmentally relevant dosages of 25, 50, 100, and 200 μg/L of SMX for 28 days. Cytotoxicity through hematology and biochemistry showed a dose-response relationship. Numerous variations were recorded in blood profile and biochemical parameters in SMX-exposed groups when compared to control. Hemoglobin, platelet, and erythrocyte levels were significantly decreased. Leukocyte level was significantly increased with values ranging from 131 to 303 (×103/μL). Changes in biochemical indices: glucose, total protein, and triglycerides showed biphasic trend, but alanine transaminase secretion was significantly increased from 25.13 to 204 U/L at higher concentration compared to control, suggesting liver damage. Spectrophotometric nitroblue tetrazolium reduction assay showed that respiratory burst activity increased as a function of SMX dose and exposure time (0.48-1.33 absorbance) ultimately leading to reduction in immunity. The present study highlights that prolonged exposure of SMX affects biochemistry, hematology, and immunohematology of fish and these biomarkers act as an effective tool for environmental risk assessment of drugs in the aquatic environment.